Pengembangan Customer Relationship Management (CRM) Sistem Informasi E-Complaint Kota XYZ - Elza Fadli Hadimulyo; Welly Purnomo; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The absence of the use of information systems in the management and handling of complaints in the XYZ city resulted in the management and handling of incoming complaints takes a longer time. This also affects the process making reports of complaints becoming inefficient. To improve the quality of complaints services in XYZ city, it is necessary to support the information system to support the management and handling complaints in XYZ city by applying the principles of CRM. This research was conducted to find out the information system built can improve the quality of complaint service in XYZ city. The information system will be built using Waterfall method and object oriented modeling. To build information systems researchers needs requirement analysis, design, implementation, and testing. Stages of needs analysis result in the depiction of business processes using BPMN and use case diagrams to model the needs and actors involved in the system. Stages of design produce activity diagrams, documentation of object interaction models into sequence diagrams, object model class diagrams, database design, algorithm design, and interface design. In the implementation stage generated information system in accordance with the design made in the previous stage. After that do white box testing using basis path testing to find out the complexity of the program code created and black box testing to test the functional requirements that are made is running as expected. To test the information system built can improve the quality of complaints service in XYZ city conducted UAT testing. The results of this study can be concluded that the information system built can improve the quality of complaints services in XYZ city.